Analysis of the Effectiveness of Quality Management Tools Aimed at Risk-Management of Organizations - Ostapenko Maria (EDP Sciences, 2021)
Risks are often associated with negative situations that can lead to threats to the continued performance of an organization. To reduce, analyze and evaluate, various methods and systems of risk management appeared, which in recent decades have become the goals of enterprises and have formed whole systems of risk management included in the main direction of modern management. In this paper, the main methods, as well as modern models of risk management, are considered, and the method for assessing and analyzing risks of an enterprise is developed. Due to flexibility and simplicity of the applied tools for creating a theoretical method, it can be integrated and adjusted to any organization’s requirements.